2011
DOI: 10.1177/039463201102400320
|View full text |Cite|
|
Sign up to set email alerts
|

The Protective Role of Catalase against Cerebral Ischemia in Vitro and in Vivo

Abstract: RN and NBM contributed equally to this manuscriptThe present study aims to assess the protective role of the antioxidant enzyme catalase (CAT) with relation to hydrogen peroxide ("202) degradation in oxygen plus water on electrophysiological and fluorescence changes induced by in vitro ischemia and on brain damage produced by transient in vivo ischemia. Neuroprotective effects of CAT were determined by means of electrophysiological recordings and confocal fluorescence microscopy in the hippocampal slice prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…(I) The figure shows · O 2 ‐ radical formation decrease measured in the CA1 hippocampal region by using fluorescent probe DHE after 1 h of superfusion, in OGD (40 min) exposed‐Tg(CAT) slices (lower) as compared with WT group (upper) ( n = 3 mice per experimental group, P < 0.05). Scale bar: 25 µm [G–I modified from Armogida et al . (2011); copyright IJIP , used with permission].…”
Section: Effects Of H2o2 On Rodent In Vitro and In Vivo Models Of Bramentioning
confidence: 99%
See 1 more Smart Citation
“…(I) The figure shows · O 2 ‐ radical formation decrease measured in the CA1 hippocampal region by using fluorescent probe DHE after 1 h of superfusion, in OGD (40 min) exposed‐Tg(CAT) slices (lower) as compared with WT group (upper) ( n = 3 mice per experimental group, P < 0.05). Scale bar: 25 µm [G–I modified from Armogida et al . (2011); copyright IJIP , used with permission].…”
Section: Effects Of H2o2 On Rodent In Vitro and In Vivo Models Of Bramentioning
confidence: 99%
“…Of note, systemic infusion of CAT failed to improve neurological deficits after complete ischaemia (Forsman et al ., 1988), but resulted in a decrease of myocardial injury following coronary ischaemia (Gardner et al ., 1983). In the light of our recent findings demonstrating a CAT‐mediated neuroprotective effect of H 2 O 2 in oxygen‐deprived brain slices of the substantia nigra, hippocampus, striatum and in an in vivo model of transient focal brain ischaemia (Geracitano et al ., 2005; Nisticò et al ., 2008; Amantea et al ., 2009), we have also investigated whether either the exogenous administration or the overexpression of CAT is protective in in vitro and in vivo brain ischaemic models (Armogida et al ., 2011). Along with previous studies, our findings indicate that hippocampal synaptic transmission was restored only when CAT (500 U·mL −1 , 15 min) was bath‐applied before a relative long period of OGD (40 min, that in control condition kills the neurons) in combination with H 2 O 2 (3 mM) (Figure 3G).…”
Section: Can the Pharmacological Modulation Of Enzymatic Pathways Leamentioning
confidence: 99%
“…It is well accepted that antioxidant enzymes, such SODs and CAT as free radical scavengers play a prominent role in neuroprotection against ischemic injury in brains. For example, ischemic brain injuries following transient global or focal ischemia in brains are apparently ameliorated in genetically engineered mouse and rat models overexpressing SOD1, SOD2, or CAT [ 48 , 49 , 50 ]. Moreover, it has been reported that enhanced levels of SOD and CAT by pretreatment with some plant extracts are closely involved in neuroprotection against ischemic injury following transient global ischemia in brains of rats and gerbils [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to SOD, knockout and overexpression of GPx influence the susceptibility to nervous system oxidative damage, without necessarily influencing normal aging ( 155 ). Knockout of CAT is relatively benign, possibly due to compensation by GPx, although overexpression of CAT is neuroprotective against ischemia ( 11 ). Interestingly, transgenic mice, which express CAT, specifically in the mitochondria, exhibit reduced effects of aging on heart, muscle, and metabolism, as well as increased longevity ( 67 , 151 , 244 , 277 , 280 ) and enhanced hippocampal-dependent memory ( 203 ).…”
Section: Antioxidant Enzymesmentioning
confidence: 99%